Acceptability of neonatal circumcision by pregnant women in KwaZulu-Natal, South Africa - Rogerio Phili; Quarraisha A. Karim (AOSIS, 2015)
Background: Studies on voluntary medical male circumcision (VMMC) have provided convincing evidence on its efficacy to provide partial protection against female-to-male HIV transmission in circumcised men. The World Health Organization and UNAIDS subsequently formulated recommendations for VMMC implementation that included implementation of neonatal medical male circumcision (NMMC) to all infants up to two months old. Knowledge regarding the acceptability of NMMC by pregnant women who are candidates for granting of consents for NMMC procedures or its ideal placement within health programmes is low. Objectives: We sought to establish NMMC acceptability by pregnant women and the feasibility of its integration within Maternal, Child and Women's Health (MCWH) programmes to inform implementation guidelines. Method: Nurses and counsellors at two public health facilities were trained to provide NMMC counselling and offer NMMC to 1778 pregnant women presenting for antenatal care services. Univariate and bivariate analyses were performed on data collected on NMMC acceptance and refusals. Thematic analysis was also performed on qualitative reasons for refusals. Results: Acceptability of NMMC by women was high (82.9%). Refusals resulted from the need for consultations with partners and/or family members prior to consenting (41.3%), fear of the procedure (23.8%), cultural reasons (15.9%) and no reasons given (15.3%). Conclusion: The acceptability of NMMC by pregnant women and its integration with MCWH services was feasible. However socio-cultural factors, including the need for further consultation prior to consenting for NMMC procedures and preference of traditional circumcision by some women, need to be addressed in order to increase uptakes.